On three species of the genus Habrocestum Simon, 1876 (Araneae: Salticidae: Hasariini) from India - Jose, Athira; Caleb, John T.d.; Sudhikumar, Ambalaparambil Vasu (Zootaxa, 2024)
Two new species of the ground-dwelling jumping spider genus Habrocestum Simon, 1876 from the wet evergreen forests of the southern Western Ghats, India are described: H. benjamin sp. nov. (♂♀) and H. swaminathan sp. nov. (♂♀). Furthermore, H. emanasakgrensis Kadam & Tripathi, 2023 is synonymized with Chinattus validus (Xie, Peng & Kim, 1993) syn. nov.. Diagnoses, digital illustrations, morphological descriptions, natural history notes and discussion are provided.